PERLINDUNGAN HUKUM BAGI PIHAK LEMAH DALAM PROSES HUKUM ACARA PERDATA - Sabet Al Banani (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The trial process aims to produce a decision that resolves disputes. In civil cases, individuals may face opponents they do not know. Civil trials often involve personal issues that cannot be resolved amicably. Many middle- and upper-class individuals resort to court proceedings, whether dealing with disputes involving family members or unknown parties. When facing wealthier opponents, individuals from lower economic backgrounds are often at a disadvantage. Although the opposing party may be guilty, they can fund the court process using their assets, leaving the less privileged party vulnerable and in need of legal protection. This creates an imbalance, where the law seems to favor the stronger party, undermining fairness in civil procedural processes. If the law were equitable, it would foster justice, ensuring the process is not perceived as biased by the public or the parties involved, reducing sensitivity surrounding legal outcomes.